Thermo and photo-oxidation of functionalized metallocene high density polyethylene: Effect of hydrophilic groups. (January 2015) - de la Orden, M.U.; Montes, J.M.; Martínez Urreaga, J.; Bento, A.; Ribeiro, M.R.; Pérez, E.; Cerrada, M.L.
Abstract: Incorporation of a small content of undecenoic acid is proposed as an approach to introduce polar groups within the macromolecular architecture of high density polyethylene-based materials in order to promote an easier degradation after their useful service life. The influence of these hydrophilic groups during thermo and photo-oxidation processes has been then evaluated by several complementary techniques. In addition to different degradation rates, distinct ratios of oxidized species (lactones, ketones, carboxylic acids, esters and aldehydes) are found depending on: a) the initial material (neat high density polyethylene or ethylene- co -undecenoic acid copolymer); b) the type of oxidation (thermo or photoinduced); and c) the absence or presence of a specific prodegradant additive. An important increase of crystallinity has been observed in the final oxidized samples, indicating that the extent of degradation is rather significant.